Neutron interferometry detection of early crack formation caused by bending fatigue in additively manufactured SS316 dogbones. (15th February 2018) - Brooks, Adam J.; Hussey, Daniel S.; Yao, Hong; Haghshenas, Ali; Yuan, Jumao; LaManna, Jacob M.; Jacobson, David L.; Lowery, Caroline G.; Kardjilov, Nikolay; Guo, Shengmin; Khonsari, Michael M.; Butler, Leslie G.
Abstract: Fatigue in selective laser melted (SLM) and conventionally manufactured stainless steel (SS) 316 dogbones was studied with neutron imaging methods for attenuation, diffraction, and scattering. Neutron attenuation tomography and Bragg edge imaging did not reveal crack formation. Conversely, to efficiently detect the microcrack evolution, two methods of grating-based neutron interferometry, Talbot-Lau and far-field, were employed. Both interferometry methods detect early crack formation via the dark-field (scattering) images, especially for porous microstructures in the range of 0.6 μm to 2 μm. The dark-field image combines sensitivity to micrometer-sized scattering centers at crack formation with sub-millimeter imaging resolution. The crack formation observed with neutron interferometry dark-field was validated post-imaging with additional fatigue cycles to fracture. Further inspection was performed by scanning electron microscopy (SEM) and optical photography. In the two fatigued dogbones, SLM and conventional crack formation was identified to within 1 mm. Graphical Abstract: Highlights: Several innovative, non-destructive neutron imaging methods observe crack formation in fatigued stainless steel dogbones Talbot-Lau and far-field interferometry show the advantages of interferometry in assessing additively manufactured samples Scattering features observed in dark-field images are shown to later grow into fracture points in the half-life dogbones The dark-field images suggest the formation of smaller pores near crack locations as confirmed by SEM